Initial Clinical Experience with Robotic Lateral Pelvic Lymph Node Dissection for Advanced Rectal Cancer - Park, Ju-A (The Korean Society of Coloproctology, 2012)
PURPOSE: This study was conducted to evaluate the technical feasibility and safety of robotic extended lateral pelvic lymph node dissection (LPLD) in patients with advanced low rectal cancer. METHODS: A review of a prospectively-collected database at Kyungpook National University Medical Center from January 2011 to November revealed a series of 8 consecutive robotic LPLD cases with a preoperative diagnosis of lateral node metastasis. Data regarding patient demographics, operating time, perioperative blood loss, surgical morbidity, lateral lymph node status, and functional outcome were analyzed. RESULTS: In all eight patients, the procedures were completed without conversion to open surgery. The mean operative time of extended pelvic node dissection was 38 minutes (range, 20 to 51 minutes), the mean number of lateral lymph nodes harvested was 4.1 (range, 1 to 13), and 3 patients (38%) were found to have lymph node metastases. Postoperative mortality and morbidity were 0% and 25%, respectively, but, there was no LPLD-related morbidity. The mean hospital stay was 7.5 days (range, 5 to 12 days). CONCLUSION: Robotic LPLD is safe and feasible, with the advantage of being a minimally invasive approach. Further large-scale studies comparing robotic and conventional surgery with long-term follow-up evaluation are needed to confirm these findings.